Return-to-sports criteria used by professional team physicians in elite athletes after hip arthroscopy - a qualitative study - Pasurka, M.; Szlufcik, M.; Theodoropoulos, J.; Betsch, M. (The Physician and Sportsmedicine, 2025)
Objectives The purpose of this study was to explore currently utilized readiness to Return to Sport (RTS) criteria after Hip Arthroscopy (HA) used in elite athletes to gain novel insights into the RTS decision-making process of professional team physicians. The authors hypothesized that even among this group of highly specialized physicians, there exists variability of measures and criteria used to determine RTS after HA.